Monitoring of in-place strength in concrete structures using maturity method – An overview. (October 2022) - Miller, Dane; Ho, Nhat-Minh; Talebian, Nima
Abstract: Quality assurance of concrete used in structures requires in-situ monitoring of early age compressive strength development. Unlike traditional approaches, accurate estimation of early age concrete strength using maturity method can be effectively used to optimise critical construction operations, prevent performance issues and even structural failure. According to the concrete maturity method, concrete strength development is strongly linked to curing temperature and relative humidity. This paper presents an overview of in-situ monitoring strength in concrete structures using the maturity method. Various maturity functions and strength-maturity relationships are summarised. Advanced technological monitoring systems, including both wired and wireless technologies, used for determining concrete strength, temperature, and maturity are discussed with an emphasis on fully automated real-time monitoring systems. Examples of applying the maturity method in monitoring of in-situ strength in various concrete structures are highlighted and compared to the traditional method (e.g. concrete cylinder testing). As a result, the maturity method is a reliable indicator of the in-situ strength to ensure the safety of various structural concrete elements during construction. The paper concludes by stressing some areas where further investigations could provide important insights into the advancements of the field.